2012
DOI: 10.15625/0866-7160/v33n3.770
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals status in sediment at Can Gio mangrove, Ho Chi Minh city, Vietnam

Abstract: NGUYÔN §×NH Tø , NGUYÔN Vò THANH ViÖn Sinh th¸i vµ Tµi nguyªn sinh vËtTrong nhiÒu n¨m trë l¹i ®©y do sö dông nhiÒu c¸c lo¹i thuèc b ¶o vÖ thùc vËt trong n«ng nghiÖp, ph¸t triÓn c«ng nghiÖp, vËn chuyÓn hµng h ¶i còng nh− viÖc ®« thÞ hãa t¨ng nhanh ® g©y « nhiÔm nhiÒu nguån n−íc do phÕ th ¶i kh«ng qua xö lý ®ae ra s«ng, theo s«ng ra biÓn g©y « nhiÔm nhiÒu vïng réng lín. Ngoµi viÖc g©y « nhiÔm m«i tr−êng, nguån n−íc, qu¸ tr×nh l¾ng ®äng, tÝch tô phÕ th ¶i trong ®ã cã nhiÒu kim lo¹i nAEng trong líp trÇm tÝch cã th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The concentration of Hg in the dammed upstream area was also higher than in the natural biosphere reserve part of the protected Can Gio mangrove forests in the southern part of Vietnam. Here, the amount of Hg varied between 0.040 and 0.048 µg/g [56]. It has been previously reported that heavy metals are adsorbed by suspended particulates and in this way they can settle down in the sediment and be remobilized into the food chain [9].…”
Section: Differences In Environmental Variables Related To Dam Effectsmentioning
confidence: 99%
“…The concentration of Hg in the dammed upstream area was also higher than in the natural biosphere reserve part of the protected Can Gio mangrove forests in the southern part of Vietnam. Here, the amount of Hg varied between 0.040 and 0.048 µg/g [56]. It has been previously reported that heavy metals are adsorbed by suspended particulates and in this way they can settle down in the sediment and be remobilized into the food chain [9].…”
Section: Differences In Environmental Variables Related To Dam Effectsmentioning
confidence: 99%